Genetic relationships among American donkey populations: insights into the process of colonization. (13th September 2015) - Jordana, J.; Ferrando, A.; Miró, J.; Goyache, F.; Loarca, A.; Martínez López, O.R.; Canelón, J.L.; Stemmer, A.; Aguirre, L.; Lara, M.A.C.; Álvarez, L.A.; Llambí, S.; et al.
Summary: This study presents the first insights into the genetic diversity and structure of the American donkey metapopulation. The primary objectives were to detect the main structural features underlying variability among American donkey populations, identify boundaries between differentiated gene pools, and draw the main colonization pathways since the introduction of donkeys into America in the 15th century. A panel of 14 microsatellite markers was applied for genotyping 350 American donkeys from 13 countries. The genetic structure of this metapopulation was analysed using descriptive statistics and Bayesian model‐based methods. These populations were then compared to a database containing information on 476 individuals from 11 European breeds to identify the most likely ancestral donor populations. Results showed the presence of two distinct genetic pools, with confluence of the two in Colombia. The southern pool showed a unique genetic signature subsequent to an older founder event, but lacked any significant influence of modern gene flow from Europe. The northern pool, conversely, may have retained more ancestral polymorphisms and/or have experienced modern gene flow from Spanish breeds. The Andalusian and, to a lesser extent, the Catalan breeds have left a more pronounced footprint in some of the American donkey populations analysed.